Assessing Postural Stability in the Concussed Athlete: What to Do, What to Expect, and When - Ruhe, Alexander (SAGE Publications, 2014)
CONTEXT: Postural stability assessment is included as part of the diagnostic and monitoring process for sports-related concussions. Particularly, the relatively simple Balance Error Scoring System (BESS) and more sophisticated force plate measures like the Sensory Organization Test (SOT) are suggested. EVIDENCE ACQUISITION: Relevant studies were identified via the following electronic databases: PubMed, MEDLINE, EMBASE, Web of Science, ScienceDirect, and CINAHL (1980 to July 2013). Inclusion was based on the evaluation of postural sway or balance in concussed athletes of any age or sex and investigating the reliability or validity of the included tests. STUDY DESIGN: Clinical review. LEVEL OF EVIDENCE: Level 4 RESULTS: Both the SOT and the BESS show moderate reliability, but a learning effect due to repetitive testing needs to be considered. Both tests indicate that postural stability returns to baseline by day 3 to 5 in most concussed athletes. While the BESS is a simple and valid method, it is sensitive to subjectivity in scoring and the learning effect. The SOT is very sensitive to even subtle changes in postural sway, and thus, more accurate than the BESS; however, it is a rather expensive method of balance testing. CONCLUSION: Both tests serve the purpose of monitoring balance performance in the concussed athlete; however, neither may serve as a stand-alone diagnostic or monitoring tool. STRENGTH OF RECOMMENDATION TAXONOMY: B